Reducing Mental Health Disparities Through Transformative Learning: A Social Change Model With Refugees and Students - Hess, Julia M. (2014)
Distribution of power and resources greatly impacts the mental health of individuals and communities. Thus, in order to reduce mental health disparities, it is imperative to address these social determinants of mental health through social change. Engaging in social change efforts requires people to critically engage with present conditions on personal, local, national and global levels and to develop knowledge, capacity, and experience with envisioning and creating more equitable conditions. This critical engagement can be fostered through a process of transformative learning. In this article, we examine the Refugee Well-being Project (RWP), a program that aims to improve the mental health of refugees in the United States. From 2007 to 2009, participants in the RWP in New Mexico were refugees from the Great Lakes region of Africa. The RWP paired undergraduate students with refugees to engage in mutual learning and advocacy. Data from in-depth qualitative interviews with 72 refugees and 53 undergraduate students suggest that participation in the RWP constituted a transformative learning experience through which refugees and students came to new understandings of the relationship between social inequities and well-being. For many, this provided an impetus to work towards change at multiple levels.